Improving Children's Communication Skills Through Puppet Card Media for Children Aged 5-6 Years - Sapna Tanjung; Masganti Sit (Jurnal Kajian dan Penelitian Umum, 2026)
This study aims to improve the communication skills of 5–6-year-old children through the use of wayang cards at RA Hj. Siti Syarifah. Unlike previous studies that primarily used pictures or storybooks, this study utilizes wayang cards as a means to encourage children's communication through storytelling, question-and-answer activities, and role-playing. The method used was Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of four stages: planning, action implementation, observation, and reflection. The study subjects were 15 children, consisting of 6 boys and 9 girls. The communication skill indicators observed included the ability to follow simple instructions, ask questions, and use language in role-playing activities. The results showed an increase in children's communication skills in each action cycle. In the pre-action phase, the average percentage of children's communication skills was 38%, categorized as Not Developing (BB). In the first cycle, this increased to 63%, categorized as Starting to Develop (MB), and in the second cycle, it reached 89%, categorized as Developing Very Well (BSB). These results indicate that the use of puppet cards is effective in improving communication skills in early childhood. This research contributes to the development of innovative and engaging learning media to enhance children's communication skills in early childhood education.